Impact of different training modalities on anthropometric outcomes in patients with obesity: A systematic review and network meta‐analysis. (23rd February 2021) - Morze, Jakub; Rücker, Gerta; Danielewicz, Anna; Przybyłowicz, Katarzyna; Neuenschwander, Manuela; Schlesinger, Sabrina; Schwingshackl, Lukas
Summary: Obesity management guidelines consistently advise aerobic training for weight loss, whereas recommendations for other training modalities are sparse. This systematic review and network meta‐analysis (NMA) aimed to compare the long‐term effects of different training modalities on anthropometric outcomes in patients with obesity. MEDLINE, Cochrane CENTRAL, and Web of Science were searched to identify the following: (1) randomized controlled trials (RCTs); (2) conducted in adults with a mean body mass index (BMI) ≥30 kg/m 2 ; (3) comparing aerobic, resistance, combined, or high‐intensity interval training head‐to‐head or to control for ≥6 months; and (4) reporting changes in body weight (BW), BMI, waist circumference (WC), fat mass (FM), or fat‐free mass (FFM). Random‐effects NMA models were fitted in a frequentist approach. GRADE framework was used to assess certainty of evidence. Thirty‐two RCTs with 4774 participants with obesity were included in this review. Aerobic training was ranked as best for improving BW, BMI, and WC and combined training for improving FM, as well as equally with resistance training most effective for improving FFM. Low to moderate certainty of evidence supports use of aerobic training to improve anthropometric outcomes in obesity, and its combination with resistance training provides additional benefit for reducing FM and increasing FFM.